2009
DOI: 10.4081/or.2009.e9
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric calcaneal fractures

Abstract: Although operative treatment of displaced, intra-articular fractures of the calcaneus in adults is generally accepted as standard practice, operative treatment for the same fractures in the skeletally immature remains controversial, potentially because the outcome for fracture types (intra- vs. extra-articular) and severity (displaced vs. nondisplaced) have been confounded in studies of children. We review herein the results of 21 displaced, intra-articular fractures in 18 skeletally immature patients, who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Ceccarelli et al, 51 when assessing adolescents aged 15–17 years with deviated intra-articular fractures, observed significantly worse results in the conservative treatment when compared with surgical treatment.…”
Section: Calcaneal Fracturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ceccarelli et al, 51 when assessing adolescents aged 15–17 years with deviated intra-articular fractures, observed significantly worse results in the conservative treatment when compared with surgical treatment.…”
Section: Calcaneal Fracturesmentioning
confidence: 99%
“…Up to 5 years of age, the mean value was 15°; between 5 and 10 years, a significant increase to 55° was observed, reaching up to 37° at 13, which is very similar to the adult value. Two retrospective series indicated good long-term results from conservative treatment of deviated intra-articular fractures 50, 51. However, degenerative changes in the subtalar joint and significant shortening of the calcaneus were observed after 12 years 47 …”
Section: Calcaneal Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly for all non-displaced or minimally displaced extra-articular calcaneal fractures (minimally displaced fractures can be considered those with 1 - 2 mm of deviation between the fragments [12]), the conservative treatment is the choice [12, 13, 16, 23]. Several authors have reported good outcomes in these cases [9, 12, 15, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Although the scientific literature is supporting operative management of calcaneal fractures in adults, there are few studies in children as calcaneal fractures are rare in this age group [2,3]. While calcaneal fractures constitute 1 to 2% of all fractures in adulthood, this occurrence rate drops sharply to 0.005% in childhood [3].…”
Section: Introductionmentioning
confidence: 99%